Neural excitation/inhibition imbalance and neurodevelopmental pathology in human copy number variant syndromes: a systematic review - Amy L. Sylvester; Eva Hensenne; Dimo Ivanov; Benedikt A. Poser; David E. J. Linden; Thérèse van Amelsvoort; Claudia Vingerhoets (Journal of Neurodevelopmental Disorders)
Abstract Cumulative evidence suggests neurodevelopmental disorders are closely related. The risk of these disorders is increased by a series of copy number variant syndromes – phenotypically heterogeneous genetic disorders, present in a minority of the population. Recent models suggest that a disruption in the balance between excitatory and inhibitory neural activity may contribute to the aetiology of neurodevelopmental disorders, and may be additionally disturbed in copy number variant syndromes. In this systematic review, the databases PubMed, Embase, and Scopus were searched for studies of excitation/inhibition imbalance in relation to neurodevelopmental disorders in human copy number variant samples. A total of 53 studies were included, representing a variety of copy number variants and research methodologies. The resulting data suggests excitation/inhibition balance is indeed disrupted in different copy number variant populations, providing insight into a putative mechanism of both idiopathic and genetic neurodevelopmental disorders. However, the high level of heterogeneity in the data set, alongside emerging techniques for excitation/inhibition assessment, prompts further investigation of this field.